Identifikasi Beban Kerja Dengan Keluhan Kelelahan Kerja Pada Pekerja Stasiun Pengisian Bahan Bakar Umum (SPBU) Di Kebun Cengkeh - Ira Sandi Tunny (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2022)
Workload is the volume of work results or records of work results which can show the volume produced by a number of employees in a particular section. Work fatigue is a condition of weakening activities, motivation, and physical fatigue to do work. This research is a quantitative research with a descriptive design which was carried out at the Clove Garden Public Fuel Filling Station (SPBU) from 19 August – 19 September 2020. The population in this study totaled 32 people with a total sample of 32 people. The sampling technique with total sampling was analyzed using univariate. The results of the research analysis were known from 32 respondents, showing that 11 respondents (33.3%) had a light workload, and 22 respondents (66.7%) had a moderate workload, most of the respondents (54.5%) were not tired, most of the respondents (45.5%) had a low level of work fatigue. It was concluded that the results of the identification indicated that the workload in the moderate category was the most felt by respondents.